From Intimacy to Currency: Self-Disclosure of Jak FM’s Sarapan Seru Radio Presenters as a Business Strategy - Rizky Kertanegara; Arius Krypton; Khairunnisa Devani Aqtus Permana Putri (CHANNEL: Jurnal Komunikasi, 2026)
Amid the dominance of digital media, radio faces sustained pressure to retain audiences and demonstrate business relevance. One distinctive asset is the on-air presenter’s capacity to build emotional closeness with listeners. This qualitative case study examines presenter self-disclosure as a communication strategy that converts into relationship currency for the industry. Data were gathered through in-depth interviews with two main presenters of the morning prime-time program Sarapan Seru on Jak FM Jakarta and analyzed thematically using a framework informed by Social Penetration, Parasocial Interaction, and Uses & Gratifications perspectives. Findings show that self-disclosure operates along two dimensions, breadth (topic variety) and depth (calibrated personal vulnerability), that jointly signal authenticity, catalyze parasocial companionship, and translate into observable participation (call-ins, direct messages/WhatsApp, voice notes, and other user-generated content). Building on these insights, the article proposes a conceptual pathway in which disclosure-driven intimacy functions as “relationship currency” that can be translated into sponsor-facing value propositions such as perceived brand-audience fit and the credibility of integrated host-read messages. The study contributes to radio and audio-media scholarship by linking relational communication mechanisms to media-economics logics, while acknowledging that commercial outcomes are inferred from qualitative insight rather than empirically measured.